Comparison of Outcome of Intracervical Foley Catheter Versus E2 in Primigravida Women for Induction of Labour - Aqsa Khalid, Rabeea Shahid, Rida Fatima, Rubab Fatimaa, Faraz Bakht, Malahat Mansoor (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Labour induction refers to the artificial initiation of the childbirth process before it begins naturally. The Foley catheter serves as a reliable option for cervical ripening and labour induction, offering an effective alternative to prostaglandins. Objective: To compare the outcome of intracervical Foley’s catheter versus prostaglandin E2 in primigravida women for induction of labour. Study Design: Randomized controlled trial Place and Duration of Study: Department of Obstetrics & Gynaecology, Sughra Shafi Medical Complex, Narowal from 15-03-2023 to 14-09-2023. Methodology: A total of70 eligible women were randomly divided into two groups of 35 in the Foley catheter group and 35 in the PGE2 group by the lottery method. Intracervical Foley’s catheter versus prostaglandin E2 effectiveness was measured as successful labour induction and mean labour duration. SPSS version 21 was used to analyze data. Results: Group A had a mean age of 25.8±3.0 years, and Group B had a mean age of 25.7±4.6 years. Success rate of induction of labour between Group A, Foley Catheter and Group B, Prostaglandin E2 was compared. In Group A, 13 (37.1%) successful induction and 22 (62.9%) failed induction. But in Group B, the success rate was quite high as 25 patients (71.4%) had successful induction (p=0.004). Group A (Foley Catheter) and Group B (Prostaglandin E2) mean labour time was statistically compared. Group A recorded increased mean labour time of 402.31± 34.01 minutes whereas Group B recorded smaller mean time of 357.60± 38.43 minutes. The p-value of 0.001 is statistically significant and signifies quicker advancement of labour in the patients induced with Prostaglandin E2 than in the patients induced with Foley catheter. Conclusion: In conclusion, prostaglandin E2 tablets proved to be significantly more effective than Foley catheters in achieving vaginal delivery within 24-48 hours among primigravida women and quicker labour progress was noted in the Prostaglandin E2-induced patients than in Foley catheter-induced patients. Keywords: Induction of labour, Primigravida, Foley catheter, PGE2